Social psychology and management : issues for a changing society - Brotherton, Christopher J. (Open University Press, 1999)
Introduction. Social psychology and management in a changing society. Individual performance at work: the problem of motivation. Groups, leadership and teams. Gender and diversity. Social psychology and technology. The rise of networked organizations and boundaryless careers.